Molecular Characterization of a Multidrug-Resistant Klebsiella pneumoniae Strain R46 Isolated from a Rabbit. (18th August 2019) - Wu, Fei; Ying, Yuanyuan; Yin, Min; Jiang, Yi; Wu, Chongyang; Qian, Changrui; Chen, Qianqian; Shen, Kai; Cheng, Cong; Zhu, Licheng; Li, Kewei; Xu, Teng; et al.
Abstract : To investigate the mechanisms of multiple resistance and the horizontal transfer of resistance genes in animal pathogens, we characterized the molecular structures of the resistance gene-related sequences in a multidrug-resistant Klebsiella pneumoniae strain R46 isolated from a rabbit. Molecular cloning was performed to clone the resistance genes, and minimum inhibitory concentrations (MICs) were measured to determine the resistance characteristics of the cloned genes and related strains. A conjugation experiment was conducted to assess the transferability of the resistance plasmids. Sequencing and comparative genomic methods were used to analyze the structures of the resistance gene-related sequences. The K. pneumoniae R46 genome consisted of a chromosome and three resistance plasmids named pR46-27, pR46-42, and pR46-270, respectively. The whole genome encoded 34 antibiotic resistance genes including a newly identified chromosome-encoded florfenicol resistance gene named mdfA2 . pR46-270, besides encoding 26 antibiotic resistance genes, carried four clusters of heavy metal resistance genes and several virulence-related genes or gene clusters. The plasmid-encoded resistance genes were mostly associated with mobile genetic elements. The plasmid with the most similarity to the floR gene-harboring plasmid pR46-27 was pCTXM-2271, a plasmid from Escherichia coli . The results of this work demonstrated that the plasmids with multidrug resistance genes were present in animal-derived bacteria and more florfenicol resistance genes such as mdfA2 could be present in bacterial populations. The resistance genes encoded on the plasmids may spread between the bacteria of different species or genera and cause the resistance dissemination.